PEMODELAN ALJABAR MAX-PLUS DAN EVALUASI KINERJA JARINGAN ANTRIAN FORK-JOIN TAKSIKLIK DENGAN KAPASITAS PENYANGGA TAKHINGGA - M. ANDY RUDHITO; SRI WAHYUNI; ARI SUPARWANTO; F. SUSILO (Mathematics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2010)
This paper aims to model and determine the service cycle completion time of noncyclic fork-joinqueueing networks with infinite buffer capacity, using max-plus algebra. The finding show that thedynamics of the noncyclic fork-join queuing networks with infinite buffer capacity can be modeledinto a matrix equation over max-plus algebra. We can also show that the service cycle completion timeof queuing networks is a max-plus eigenvalues of the matrix in the equation.slklsklslsllsllllllllllllllllllllll